(untitled) (Ann Arbor, 1986)
This book introduce opening statement, stimulating and managing corporate entrepreneurship, the auto industry connection. Honda's approach to a mature industry. Entrepreneurship in he supplier industry...
Keywords: Công nghiệp ô tô và thương mại,Automobile industry and trade; Quản trị,Hội nghị,Management,Congresses